2022
DOI: 10.3389/fgene.2022.1048761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes in late-onset major depressive disorder through a co-expression network module

Abstract: Late-onset major depressive disorder (LOD) increases the risk of disability and suicide in elderly patients. However, the complex pathological mechanism of LOD still remains unclear. We selected 10 LOD patients and 12 healthy control samples from the GSE76826 dataset for statistical analysis. Under the screening criteria, 811 differentially expressed genes (DEGs) were screened. We obtained a total of two most clinically significant modules through the weighted gene co-expression network analysis (WGCNA). Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previously, the association between the CD79A and MDD was few explored. Yao et al found that CD79A could be used as the accurate diagnostic indicators of late-onset MDD [ 63 ], while the molecular mechanism deserved further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the association between the CD79A and MDD was few explored. Yao et al found that CD79A could be used as the accurate diagnostic indicators of late-onset MDD [ 63 ], while the molecular mechanism deserved further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Although the mutation rate of IGLL5 did not change with age, [23] Yao et al have shown that the low expression level of IGLL5 is a good diagnostic in elderly patients with late-onset major depressive disorder which increases the risk of suicide and disability in olds. [24] Therefore, we speculated that IGLL5 has a vital role in staying healthy for elders. Our study found that IGLL5 showed a down-regulated level in elders with a great ROC score (AUC value > 0.7), further illustrating the potential of IGLL5 as a biomarker of health for elders.…”
Section: Discussionmentioning
confidence: 99%